+0  
 
0
482
2
avatar

simpllify the given algebraic expresion: 5-8[8-(6y-7)]

Guest Jun 10, 2015

Best Answer 

 #2
avatar+94203 
+10

5-8[8-(6y-7)]

=5 - 8[8   -1(6y-7)]

=5 -8 [8   -1*6y-1*-7  ]

=5 - 8[8    -6y    +7     ]

=5 - 8[8+7-6y]

=5 - 8[15-6y]

=5  -8*15  -8*-6y

=5 - 120 + 48y

=  48y -115

 

Just as anon found :)

Melody  Jun 10, 2015
 #1
avatar
+5

-115+48y

Guest Jun 10, 2015
 #2
avatar+94203 
+10
Best Answer

5-8[8-(6y-7)]

=5 - 8[8   -1(6y-7)]

=5 -8 [8   -1*6y-1*-7  ]

=5 - 8[8    -6y    +7     ]

=5 - 8[8+7-6y]

=5 - 8[15-6y]

=5  -8*15  -8*-6y

=5 - 120 + 48y

=  48y -115

 

Just as anon found :)

Melody  Jun 10, 2015

24 Online Users

avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.